Product distribution from microwave pyrolysis of automotive paint sludge - Nor Faizah Syed Abdul Rahman, Syarifah; Ab Rahman, Norazah; Shawalliah Idris, Siti; Fitrah Abu Bakar, Noor; Ariff Za’bar, Johan; Januri, Zakiuddin (International Journal of Engineering and Technology, 2018)
Production of liquid, gas and solid from microwave pyrolysis of automotive paint sludge (APS) with addition of activated carbon as microwave absorber was investigated at different microwave (MW) power and amount of activated carbon. The microwave pyrolysis was conducted at three microwave powers of 600, 700 and 800 Watt (W) with 0 %, 10 % and 20 % (from automotive paint sludge weight) activated carbon. Increment of microwave power increased the gas yield with the highest yield was at 800 W due to high process temperature offered at high microwave power while the maximum solid and pyrolytic oil yields were obtained at 600 W due to low process temperature offered by low microwave power. However, highest solid yield at 600 W with 0 % activated carbon loading indicating incomplete pyrolysis process. The best amount of activated carbon loading was 10 % for the highest pyrolytic oil production whereas maximum gas yield was obtained at activated carbon loading of 20 %. Â Â